MED12-related XLID disorders are dose-dependent of immediate early genes (IEGs) expression. (24th March 2017) - Donnio, Lise-Marie; Bidon, Baptiste; Hashimoto, Satoru; May, Melanie; Epanchintsev, Alexey; Ryan, Colm; Allen, William; Hackett, Anna; Gecz, Jozef; Skinner, Cindy; Stevenson, Roger E.; de Brouwer, Arjan P.M.; et al.
Abstract: Mediator occupies a key role in protein coding genes expression in mediating the contacts between gene specific factors and the basal transcription machinery but little is known regarding the role of each Mediator subunits. Mutations in MED12 are linked with a broad spectrum of genetic disorders with X-linked intellectual disability that are difficult to range as Lujan, Opitz-Kaveggia or Ohdo syndromes. Here, we investigated several MED12 patients mutations (p.R206Q, p.N898D, p.R961W, p.N1007S, p.R1148H, p.S1165P and p.R1295H) and show that each MED12 mutations cause specific expression patterns of JUN, FOS and EGR1 immediate early genes (IEGs), reflected by the presence or absence of MED12 containing complex at their respective promoters. Moreover, the effect of MED12 mutations has cell-type specificity on IEG expression. As a consequence, the expression of late responsive genes such as the matrix metalloproteinase-3 and the RE1 silencing transcription factor implicated respectively in neural plasticity and the specific expression of neuronal genes is disturbed as documented for MED12/p.R1295H mutation. In such case, JUN and FOS failed to be properly recruited at their AP1-binding site. Our results suggest that the differences between MED12-related phenotypes are essentially the result of distinct IEGs expression patterns, the later ones depending on the accurate formation of the transcription initiation complex. This might challenge clinicians to rethink the traditional syndromes boundaries and to include genetic criterion in patients' diagnostic.